Primary Myelofibrosis in the Prefibrotic Stage Presenting as Portal, Splenic, and Superior Mesenteric Vein Thrombosis: A Case Report and Review of the Literature - Dias,Emanuel (2022)
Abstract Introduction: Myeloproliferative neoplasms are the most common cause of splanchnic vein thrombosis in the absence of cirrhosis or nearby malignancy. Case Presentation: A 31-year-old male presented to the emergency department with epigastric pain associated with mild thrombocytosis and elevated levels of aminotransferases, lactate dehydrogenase, and C-reactive protein. Contrast-enhanced abdominal computed tomography revealed splanchnic venous thrombosis that involved the portal, splenic, and superior mesenteric veins, without signs of chronic liver disease. Anticoagulation with warfarin was immediately started. Diagnostic work-up was remarkable for the presence of the JAK2 V617T mutation and hypercellular bone marrow, with increased myeloid cells and atypical megakaryocytes, consistent with primary myelofibrosis in a prefibrotic stage. No other hypercoagulable conditions were identified. Discussion: We present a rare case of primary myelofibrosis in the prefibrotic stage presenting as portal-splenic-superior mesenteric vein thrombosis. This demonstrates that extensive splanchnic vein thrombosis may be the onset manifestation of myeloproliferative neoplasms, even in early stages and in the absence of concomitant hypercoagulable conditions. The presence of the JAK2 mutation is an important prothrombotic risk factor that can, per se, contribute to large venous thrombosis.